Multifrequency Behaviour of the Gamma-Ray Binary System PSR B1259-63: Modelling the FERMI Flare - Brian van Soelen; Pieter J. Meintjes (Acta Polytechnica CTU Proceedings)
This paper presents a brief overview of the multifrequency properties of the gamma-ray binary system PSR B1259-63 from radio to very high energy gamma-rays. A summary is also presented of the various models put forward to explain the Fermi "flare" detected in 2011. Initial results are presented of a new turbulence driven model to explain the GeV observations.